Dyslipidemia in Postmenopausal Women: A Case Control Study - Das, Joyabrata; Sharma, Julan Das; Mazumder, Subash; Alam, Kazi Towhidul; Sarkar, Shomen; Hossain, Istiaque (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Menopause is a natural process. After menopause the morbidity and mortality from cardiovascular disease are increased. Lack of oestrogen protection, aging effect, increased body weight, android pattern of body fat distribution seems to be the major cause. In post menopausal women, there is an increased tendency for body fat deposition in the abdominal region that leads to low HDL and increased LDL. The aim of thy study is to document the serum lipid abnormality in obese postmenopausal women and to compare the lipid status between obese and non-obese postmenopausal women. Methods: This comparative study was conducted at the Department of Medicine, SMCH from Oct 2010 to Sept 2011 for duration of 1 year. After taking history, physical examination weight and height were taken, body mass index (BMI), waist hip ratio (WHR) were calculated and 4 ml of venous blood were taken from all subjects after 12-hour overnight fasting. Results: It was observed significantly positive correlation between TC, LDL level and W/H ratio and significantly negative correlation between HDL level and W/H ratio and significantly positive correlation between TG, TC, LDL, and BMI and significantly negative correlation between HDL and BMI. It was also observed significantly positive correlation between TG and WC, TC and WC, LDL and WC and significantly negative correlation between HDL and WC. Conclusion: It can be concluded from this study that mixed type of hyperlipidemia is present in postmenopausal women. Dyslipidemia is more pronounced in central obese postmenopausal women. Dyslipidemia is significantly correlated with WHR, waist circumference, and BMI. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.32 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 7-12